Functionalized MXene fiber electrode for the electrochemical sensing of urinary ammonia - Yu Liu; Xu Zeng; Yulong Wu; Habib Ullah Khan; Fei Xiao; Bao Yu Xia; Yimin Sun (Advanced Sensor and Energy Materials, 2024)
The development of technologically advanced fiber-based flexible microelectrodes has been of extensive research interest in healthcare systems because of their unique construction and synergistic effect on multifunctional properties. In this work, we constructed functional MXene fiber (MXF) by a simple and versatile wet spinning method, and then, a well-aligned ZIF-67 nanoarray was grown in situ on the surface. Using the chemical vapor deposition (CVD) method, carbon nanotubes (CNTs) were produced on MXF via the pyrolysis of ZIF-67 and melamine. Finally, Pt nanoparticles were electrodeposited on the CNTs forest, and a Pt@CNTs/MXF electrode was obtained. Owing to the plethora of surface active sites and the synergistic effects between MXene, CNTs, and Pt nanoparticles, the as-fabricated fiber electrode enabled the precise detection of ammonia under alkaline conditions via differential pulse voltammetry (DPV), which exhibited a linear range of 0.1 μM–10 mM and a detection limit of 73.2 nM. Due to their good performance in ammonia detection, Pt@CNTs/MXF electrodes could be adopted to determine the ammonia concentration in urine for clinical estimation, which provides a practical approach for the diagnosis of urinary ammonia-associated diseases.